2022
DOI: 10.3390/plants11141884
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Studies and Ultrastructure of Vigna sinensis L. and Helianthus annuus L. under Varying Levels of Nitrogen Supply

Abstract: This experiment was conducted to investigate the effects of different nitrogen fertilizers (potassium nitrate and/or urea) on shoot parameters, relative growth rate, net assimilation rate, and nitrogen fractions, as well as to conduct transmission electron microscopy, of Vigna sinensis L. (cowpea) and Helianthus annuus L. (sunflower) leaves. A general improvement was recorded in the shoot parameters of the two plants, except for a decrease in the net assimilation rate by treatment of the two plants with 100% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…Fraction C corresponds to N linked to lignin, tannin-protein complexes, and merad products, which are highly resistant to enzymes produced by microorganisms in the rumen and are considered unusable for animals ( Sniffen et al., 1992 ). In our study, it was found that fraction C decreased with an increase in N fertilization level, which was consistent with the results of previous studies ( Alharbi et al., 2022 ). However, the fraction C content showed a trend of increasing and then decreasing with an increase in P application because P fertilization decreased the acid detergent fiber content in alfalfa, which in turn decreased the fraction C content ( Zhang et al., 2014 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Fraction C corresponds to N linked to lignin, tannin-protein complexes, and merad products, which are highly resistant to enzymes produced by microorganisms in the rumen and are considered unusable for animals ( Sniffen et al., 1992 ). In our study, it was found that fraction C decreased with an increase in N fertilization level, which was consistent with the results of previous studies ( Alharbi et al., 2022 ). However, the fraction C content showed a trend of increasing and then decreasing with an increase in P application because P fertilization decreased the acid detergent fiber content in alfalfa, which in turn decreased the fraction C content ( Zhang et al., 2014 ).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, SOLP and favorable growth conditions are improved by N supply ( Sugiyama et al., 1984 ). Previous studies have shown that soluble protein and NPN content increased with increasing levels of N fertilization ( Alharbi et al., 2022 ). In our study, NPN and SOLP content increased with increasing N content at the same P fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the optimal level of mineral nitrogen and plant density are just two of the many agricultural practices that determine the productivity of onions. Nitrogen fertilizer is very important element for all living processes in enhancing the productivity in the plant [7]. It is the limiting nutrient and very important element in agricultural production.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen is a significant element for increasing bulb size and yield in onions and plays an important role in achieving the highest possible yield. It is an important element for many important substances such protein and nucleic acids [7][8][9][10]. An attempt has been made by several workers to find out the optimum plant spacing and nitrogen fertilizer for onion plants to maximize total yield with the best quality and improve storability, especially under old land conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There is a considerable danger of nitrate leaching losses and a low N fertilizer usage efficiency in onion (Allium cepa L.) production because of the plants' shallow and sparse root systems (Geisseler et al, 2022). Nitrogen is an essential elementary constituent of numerous important substances such as amino acids, protein, and nucleic acids (Alharbi et al, 2022;Mohamed et al, 2022;Omar et al, 2022;Galal et al, 2023). There are two benefits to using the optimal amount of space between plants or plant populations, this reduces the likelihood of plants having to compete for scarce resources like water, nutrients, and sunlight.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%